Conjunctivitis Related to not Severe COVID-19: A Case Report. (19th May 2021) - Marquezan, Maria Carolina; Marquezam, Joao Paulo; Nascimento, Heloisa; Chalita, Maria Regina; de Freitas, Denise; Belfort, Rubens
ABSTRACT: Purpose: The purpose of this article is to report a bilateral conjunctivitis case in a patient with confirmed 2019 novel coronavirus disease (COVID-19). Case report/observations: A 24-year-old healthy man developed severe conjunctivitis in his right eye, followed by his left eye 4 days after fever and myalgia. He reported yellowish conjunctival discharge, foreign body sensation, redness, and tearing, and those symptoms were resolved in 10 days. Analyses of nasopharyngeal secretions identified SARS-CoV-2 by polymerase chain reaction (PCR). Conclusion: Mild COVID-19 can cause severe bilateral conjunctivitis. The ophthalmologist may be aware of conjunctival secretions, a possible path of infection, during eye checkup.